(untitled) (Scientific journal of the Fergana State University, 2024)
In the present work, the conversion and output characteristics of a semiconductor-plasma gas discharge system are studied experimentally. This system, otherwise called a gas-discharge cell, is additionally equipped with a metal-grid electrode. In this case, the gas-discharge gap is divided into two parts: photodetector-grid and grid-shield. Such a construction, described in the present paper, contributes to the current amplification of the plasma. The experimentally studied dependence of the output signal power on the grid-shield current (conversion characteristic) shows that the curves have a sublinear character. The dependence of the output signal power on the input signal power value (output characteristic) is super linear. As a result of these studies, it is possible to register weak (less than 10-7 W/sm2) infrared radiation of objects.